The Ethnography of reading - Boyarin, Jonathan (University of California Press, 1993)
Writing, the subject of much innovative scholarship in recent years, is only half of what we call literacy. The other half, reading, now finally receives its due in these groundbreaking essays by a distinguished group of anthropologists and literary scholars.